2015
DOI: 10.1038/cr.2015.34
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the neutralization of hepatitis E virus by a cross-genotype antibody

Abstract: Hepatitis E virus (HEV), a non-enveloped, positive-sense, single-stranded RNA virus, is a major cause of enteric hepatitis. Classified into the family Hepeviridae, HEV comprises four genotypes (genotypes 1-4), which belong to a single serotype. We describe a monoclonal antibody (mAb), 8G12, which equally recognizes all four genotypes of HEV, with ~2.53-3.45 nM binding affinity. The mAb 8G12 has a protective, neutralizing capacity, which can significantly block virus infection in host cells. Animal studies with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 41 publications
3
64
0
1
Order By: Relevance
“…In this work, a well characterized mouse neutralizing monoclonal antibody 8G12, which was shown to efficiently block the binding of naturally acquired anti-HEV antibodies to Hecolin Ò antigen p239, 27 was applied to develop a competitive ELISA assay to detect 8G12-like antibodies in serum samples. With serial serum samples collected from participants enrolled in a HEV vaccine clinical trial, we could detect 8G12-like antibody in all participants vaccinated from Hecolin Ò and HEV vaccine (Changchun), through the titers at prime vaccination varied in each participant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, a well characterized mouse neutralizing monoclonal antibody 8G12, which was shown to efficiently block the binding of naturally acquired anti-HEV antibodies to Hecolin Ò antigen p239, 27 was applied to develop a competitive ELISA assay to detect 8G12-like antibodies in serum samples. With serial serum samples collected from participants enrolled in a HEV vaccine clinical trial, we could detect 8G12-like antibody in all participants vaccinated from Hecolin Ò and HEV vaccine (Changchun), through the titers at prime vaccination varied in each participant.…”
Section: Discussionmentioning
confidence: 99%
“…22,26 Among these mAbs developed by Zhang J and Gu Y. et.al, broad neutralizing mAbs 8H3, 8C11, 8G12 recognize the conserved residues in the E2s dimerization region on ORF2 and can protect macaque rhesus from HEV challenge. 23,27 Previous studies showed that 8G12 can significantly block the binding of HEV convalescent sera as well as Hecolin Ò vaccinated sera from human and macaques rhesus to HEV ORF2 protein. 27 The rare predominant existence of 8G12 competitive antibodies (8G12-like antibodies) in serum indicated that most neutralizing antibodies elicited by HEV natural infection or Hecolin Ò vaccination might recognize similar epitope as 8G12 or epitopes in the vicinity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction of hepatitis E morbidity and mortality depended on vaccine prevention and effective diagnosis. Knowledge of epitopes of HEV was essential for vaccine preparation and diagnostic development [22]. The detection of specific antibodies in serum is one of the main diagnostic methods, and there is a growing number of serological assays for antibody detection.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pORF 2 containing most immunogenic sites has been widely used for HEV immunological study, with a conformation-dependent character [25]. The structural basis of an immunogen to elicit neutralizing and protective antibodies is the neutralizing epitope, which is the main target of hepatitis E vaccine development [22]. We have previously reported that the p166 protein, a truncated protein of pORF 2 , can model HEV neutralizating epitope(s), and antibodies raised against p166 could cross-neutralize different genotypes of HEV [26].…”
Section: Discussionmentioning
confidence: 99%